Regimes of Expectations: An Active Inference Model of Social Conformity and Human Decision Making - Constant, Axel; Ramstead, Maxwell J. D.; Veissière, Samuel P. L.; Friston, Karl (Frontiers in Psychology, 2019)
How do humans come to acquire shared expectations about how they ought to behave in distinct normalised social settings? This paper offers a normative framework to answer this question. We introduce the computational construct of ‘deontic value’ – based on active inference and Markov decision processes – to formalise conceptions of social conformity and human decision-making. Deontic value is an attribute of choices, behaviours, or action sequences that inherit directly from deontic cues in our econiche (e.g., red traffic lights); namely, cues that denote an obligatory social rule. Crucially, the prosocial aspect of deontic value rests upon a particular form of circular causality: deontic cues exist in the environment in virtue of the environment being modified by repeated actions, while action itself is contingent upon the deontic value of environmental cues. We argue that this construction of deontic cues enables the epistemic (i.e., information-seeking) and pragmatic (i.e., goal- seeking) values of any behaviour to be ‘cached’ or ‘outsourced’ to the environment, where the environment effectively ‘learns’ about the behaviour of its denizens. We describe the process whereby this particular aspect of value enables learning of habitual behaviour over neurodevelopmental and transgenerational timescales.